Blended Sewage SludgePalm Kernel Expeller to Enhance the Palatability of Black Soldier Fly Larvae for Biodiesel Production - Ratchaprapa Raksasat; Kunlanan Kiatkittipong; Worapon Kiatkittipong; Chung Yiin Wong; Man Kee Lam; Yeek Chia Ho; Wen Da Oh; I Wayan Koko Suryawan; Jun Wei Lim (My University, 2021)
Black soldier fly larvae (BSFL) have been employed for valorizing organic waste materials as the larvae are able to consume organic waste and transform it into valuable larval biomass. In this study, BSFL were found to potentially reduce blended sewage sludge. The addition of palm kernel expeller (PKE) fortified the protein and lipid content in blended sewage sludge substrates, leading to larval growth enhancement. In addition, the larval weight also influenced the lipid yield and fatty acid methyl ester (FAME) profile. However, the optimum ratio of sewage sludge to PKE had to be determined as excess PKE content could become a threat to larval growth by contributing to the reduction of non-fiber carbohydrates content in the feed, thereby resulting in the decrease in lipid yield and FAME content. In this work, a sewage sludge to PKE ratio of 2:3 proffered the highest larval weight gained at 46.99 ± 2.09 mg/larva. Meanwhile, a proportion of 3:2 of sewage sludge to PKE was able provide the highest lipid yield of 17 ± 1.77%. Furthermore, the FAME profile revealed the presence of a significant amount of saturated and monosaturated fatty acids, indicating a good quality biodiesel. Thus, BSFL-based biodiesel fed with blended sewage sludge and PKE could be utilized for producing a high quality biodiesel. However, further improvement on the amount of lipid yield and FAME content should be further investigated.
Keywords: Sewage sludge; Insect Utilization and Effects